Pembelajaran Akhlak dan Etika (Studi Kasus di Universitas Indraprasta PGRI Jakarta): doi 10.58569/jies.v1i2.581 - Shindy , Mohamad; Maskur , Abu (Journal of Islamic Education Studies, 2023)
This study discusses the teaching of morals and ethics to morals and ethics lecturers, namely the PAKEM system (Active, Creative, Effective and Fun Learning) with lecture, discussion, debriefing and assignment methods. The purpose of this learning method is to guide students to implement this learning into their daily behavior, and students are also able to clearly understand what has been taught in morals and ethics learning, so they can practice good deeds and stay away from bad deeds.